ISOTOPIC COMPOSITIONS OF OXYGEN, IRON, CHROMIUM, AND NICKEL IN COSMIC SPHERULES: TOWARD A BETTER COMPREHENSION OF ATMOSPHERIC ENTRY HEATING EFFECTS - Engrand C.; McKeegan K.D.; Leshin L.A.; Herzog G.F.; Schnabel C.; Nyquist L.E.; Brownlee D.E. (My University, 2005)
Large, correlated, mass-dependent enrichments in the heavier isotopes of O, Cr, Fe, and Ni are observed in type-I (metal/metal oxide) cosmic spherules collected from the deep sea. Limited intraparticle variability of oxygen isotope abundances, typically <5‰ in δ18O, indicates good mixing of the melts and supports the application of the Rayleigh equation for the calculation of fractional evaporative losses during atmospheric entry. Fractional losses for oxygen evaporation from wüstite, assuming a starting isotopic composition equal to that of air (δ18O = 23.5‰; δ17O = 11.8‰), are in the range 55%–77%, and are systematically smaller than evaporative losses calculated for Fe (69%–85%), Cr (81%–95%), and especially Ni (45%–99%). However, as δ18O values increase, fractional losses for oxygen approach those of Fe, Cr, and Ni indicating a shift in the evaporating species from metallic to oxidized forms as the spherules are progressively oxidized during entry heating. The observed unequal fractional losses of O and Fe can be reconciled by allowing for a kinetic isotope mass-dependent fractionation of atmospheric oxygen during the oxidation process and/or that some metallic Fe may have undergone Rayleigh evaporation before oxidation began.